MANAJEMEN PENGELOLAAN APLIKASI ZAKAT SiMBA PADA BADAN AMIL ZAKAT NASIONAL DI KALIMANTAN TIMUR - Pancasilawati, Abnan (Collegium Studiosum Journal, 2023)
This research was motivated by the existence of the SiMBA zakat application at BAZNAS in East Kalimantan, however the operation of this zakat application has not been effective and efficient and is only operated by four daily implementers, so there is no special section that manages this application. This research is also qualitative field research. with data collection techniques in the form of observations at 3 (three) research loci, interviews with SiMBA zakat application managers, and documents related to the research. The results of this research are, first: management of the SiMBA zakat application at BAZNAS Balikpapan City, second: obstacles to the management of the SiMBA zakat application come from two factors, namely internal and external, the internal factor is the incomplete data entered by the SiMBA zakat application operator.